A low serum IGF-1 is correlated with sarcopenia in subjects with type 1 diabetes mellitus: Findings from a post-hoc analysis of the iDIAMOND study. (September 2021) - Hata, Sonyun; Mori, Hiroyasu; Yasuda, Tetsuyuki; Irie, Yoko; Yamamoto, Tsunehiko; Umayahara, Yutaka; Ryomoto, Kayoko; Yoshiuchi, Kazutomi; Yoshida, Sumiko; Shimomura, Iichiro; Kuroda, Akio; Matsuhisa, Munehide
Highlights: The factors associated with sarcopenia in type 1 diabetes (T1DM) have not been clarified. IGF-1 plays a crucial role in skeletal muscle growth, differentiation, and regeneration. The z-score of IGF-1 was significantly lower in T1DM than non-T1DM. The z-score of IGF-1 was associated with sarcopenia and a low skeletal muscle mass in T1DM. Abstract: Aim: Our previous study revealed that sarcopenia was frequently observed in subjects with type 1 diabetes mellitus (T1DM). However, the factors associated with sarcopenia that are related to T1DM have not yet been clarified. Insulin-like growth factor-1 (IGF-1) has been shown to play a role in skeletal muscle growth, differentiation, and regeneration. The present study, therefore, investigated the association between the serum IGF-1 level and sarcopenia and low skeletal muscle mass in subjects with T1DM. Methods: This cross-sectional study enrolled subjects with T1DM (n = 168) and without diabetes (n = 59) who had had their clinical data on serum IGF-1 collected in the iDIAMOND study. Results: The z-score of serum IGF-1 was significantly lower in the subjects with T1DM than that in those without diabetes (p < 0.001). Among subjects with T1DM, the z-score of serum IGF-1 was significantly lower in sarcopenic subjects than in non-sarcopenic subjects. The multivariable logistic regression analysis showed that the serum IGF-1 z-score was an independent determinant of sarcopenia and a low skeletal muscle mass index, but not low grip strength nor slow gait speed in subjects with T1DM. Conclusions: A low serum IGF-1 level is correlated with sarcopenia and low skeletal muscle mass in subjects with T1DM.